Observation of a fully non-inductive H-mode regime dominated by the sporadic-small edge-localized modes in EAST with a tungsten divertor. (17th June 2019) - Zhang, Heng; Chen, Ran; Xu, Guosheng; Wang, Yifeng; Li, Erzhong; Qian, Jinping; Ye, Yang; Yang, Qingquan; Zhang, Ling; Duan, Yanmin; Li, Yingying; Zhang, Tao; et al.
Abstract: Here we report a fully non-inductive H-mode operation with a sporadic-small-edge-localized mode(ELM)-dominant pedestal realized in EAST with a tungsten divertor, where the normalized electron collisionality at the pedestal top is estimated below unity. This is regarded as the expansion and/or supplement of our previous research having been preliminarily reported (section 4.2 in (B N Wan et al 2017 Nucl. Fusion 57 102019)) in the EAST overview article contributed to the special issue on FEC 2016 summaries and overviews. In this operation, spontaneous avoidance of large ELMs is realized reproducibly, for the first time on EAST, at a lower collisionality (below unity) at the pedestal top, profiting from high heating power. Besides, this regime shows the well controlled bulk plasma density and light impurity concentration, good energy confinement with H 98, (y2)  ≃ 1, together with a loop voltage very close to zero. All of these features are considered critical to a steady-state operation with high performance, which EAST is on target to demonstrate in the near future in support to the International Thermonuclear Experimental Reactor (ITER). However, this operation regime suffers a continuous accumulation of medium-/high- Z impurities, which may seriously limit its sustainability. The resonant magnetic perturbation (RMP) with a dominant toroidal mode number n  = 1 has been employed for assisting exhaust of heavy impurities, which is, unfortunately, not successful since the RMP with an effective poloidal spectrum always brings back large ELMs. This scenario transits to an ELM H-mode regime as plasma current is decreased, and elimination of large ELMs is well reproduced by ELITE simulation. Finally, we present a discussion on the potential mechanism eliminating large ELMs, which seems to highlight the LHW-induced profound change in edge magnetic topology.